Investigation of functionalization effect of carbon nanotubes as supercapacitor electrode material on hydrogen evolution side-reaction by scanning electrochemical microscopy. (10th October 2022) - Liu, Xuanli; Lu, Zhenjie; Pan, Haoran; Cheng, Junxia; Dou, Jinxiao; Huang, Xinning; Chen, Xingxing
Abstract: It is indeed particularly important in aqueous supercapacitors to avoid any gas evolution due to safety concerns. Nevertheless, limited research has been concentrated on those side reactions, but with more focus on the advancement of the intrinsic electrochemical properties of supercapacitor electrode materials. Herein, we report for the first time to apply high-resolution scanning electrochemical microscopy (SECM) in elucidating hydrogen evolution side reaction occurred during the charge process of supercapacitor electrodes. By taking CNTs functionalized with or without oxygen groups as the exemplary electrode materials, at first we applied conventional analytical methods to demonstrate their difference in supercapapcitor behavior. Subsequently, SECM was specifically introduced to investigate the local reactivity and conductivity of the CNT samples at submicrometer scale. Prominently, SECM was demonstrated to be capable of in-depth understanding the type of side reactions taken placeon the CNT surfaces. This report offers a new avenue to extend SECM application into assessment of supercapacitor safety performance.